2019
DOI: 10.3390/ani9040176
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Detailed Protein Composition of Cow Milk Predicted from a Large Database of Mid-Infrared Spectra

Abstract: This study aimed to investigate factors affecting protein fractions, namely α-casein (α-CN), β-casein (β-CN), κ-casein (κ-CN), β-lactoglobulin (β-LG) and α-lactalbumin (α-LA) predicted from milk infrared spectra in milk of dairy and dual-purpose cattle breeds. The dataset comprised 735,328 observations from 49,049 cows in 1782 herds. Results highlighted significant differences of protein fractions in milk of the studied breeds. Significant variations of protein fractions were found also through parities and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 34 publications
6
27
1
6
Order By: Relevance
“…A constant decrease of k-casein was observed through the entire lactation. The whey protein, α-lactalbumin and βlactoglobulin decreased until 75 DIM and increased during the remaining part of lactation (Franzoi et al, 2019). In our study the caseins reached a maximum in mid lactation.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…A constant decrease of k-casein was observed through the entire lactation. The whey protein, α-lactalbumin and βlactoglobulin decreased until 75 DIM and increased during the remaining part of lactation (Franzoi et al, 2019). In our study the caseins reached a maximum in mid lactation.…”
Section: Resultssupporting
confidence: 55%
“…In our study the content of caseins was higher than in Dutch Holstein-Friesians. Franzoi et al, (2019)observed that the proportion of αcasein and β-lactoglobulin in Italian Holstein-Friesian breed (41.64% and 5,91% respectively) was lower compared with results of Schopen et al, 2009 in first-parity Dutch-Holstein-Friesian cows, whereas β-casein was higher compared with the same study (30.44% and 27.7%, respectively). Franzoi et al, 2019 considered that such difference can be attributed to the different cow parities and lactation stages including the sampling, to diversities in farming system and area.…”
Section: Resultsmentioning
confidence: 60%
“…The prediction quality reported in the validation set for Ca, Mg, Na, and P is presented in Table 5. Model performances were satisfactory to predict Ca and P (R 2 > 0.67) in Soyeurt et al (2009); Toffanin et al (2015), Visentin et al (2016), and Franzoi et al (2019). But the same minerals were poorly predicted (R 2 < 0.55) by Gottardo et al (2015); Bonfatti et al (2016), Malacarne et al (2018), and Fleming et al (2019).…”
Section: Milk Compositionmentioning
confidence: 93%
“…The case study area was Bolzano Province, which is characterized by small-scale farms with traditional livestock feeding (forage or hay and concentrates). Moreover, approximately 20% of the herds are transhumed to mountain pastures in the summer season [14,15].…”
Section: Data Collectionmentioning
confidence: 99%